Evaluation of the effects of Uncaria rhynchophylla alkaloid extract on LPS-induced preeclampsia symptoms and inflammation in a pregnant rat model - Liang-Zhi Wu; Xiao-Min Xiao (Brazilian Journal of Medical and Biological Research, 2019)
Excessive pro-inflammatory cytokines result in adverse pregnancy outcomes, including preeclampsia-like phenotypes, and fetal growth restriction. Anti-inflammation might be an effective therapy. The aim of this research was to investigate whether Uncaria rhynchophylla alkaloid extract (URE), a highly safe anti-inflammation constituent of the herb, can inhibit inflammation and improve clinical characteristics of preeclampsia in a lipopolysaccharide (LPS)-induced preeclampsia rat model. The rat model was established by daily administration of LPS (1 μg/kg body weight per day) from gestational day (GD) 14 to 19. Different doses of URE (35, 70, and 140 mg/kg body weight per day) were administered from GD 14 to GD 19. The effects of URE on proteinuria, maternal hypertension, pregnancy outcomes, as well as pro-inflammatory cytokines levels in serum and placenta were measured. High-dose URE (HURE) treatment decreased LPS-induced mean 24-h proteinuria and systolic blood pressure, and increased fetal weight, placental weight, and the number of live pups (P<0.05). Moreover, increased serum and placental levels of interleukin (IL)-6, IL-1β, tumor necrosis factor-α, and interferon-γ in the LPS-treated group were obviously inhibited after HURE administration (P<0.01). URE improved preeclampsia symptoms and mitigated inflammatory responses in the LPS-induced preeclampsia rat model, which suggests that the anti-inflammation effect of URE might be an alternative therapy for preeclampsia.